Viscosity enhancement of self-consolidating cement-tailings grout by biomass fly ash vs. chemical admixtures. (18th July 2022) - Jin, Jiaxu; Zhang, Guosen; Qin, Zhifa; Liu, Tao; Shi, Jinyan; Zuo, Shenghao
Highlights: Effect of biomass fly ash in self-consolidating CTG was compared with chemical admixtures. The optimal content of biomass fly ash improved the workability and strength of CTG. Cement replacement by biomass fly ash showed economic and environmental benefits. Abstract: The current paper investigates the feasible use of biomass fly ash (BFA) for viscosity enhancement of self-consolidating cement-tailings grout (CTG) in comparison with chemical admixtures. The workability and stability of fresh CTG mixtures and mechanical properties, drying shrinkage, and water absorption of hardened CTGs are measured and analyzed. Results indicate that the effects of BFA as a partial cement replacement are dependent on the mass fractions of CTGs. At low mass fractions (i.e. 50% and 60%), the incorporated BFA improves the workability and mechanical strength, but reduces the stability of CTGs; At a high mass fraction of 70%, BFA reduces the workability and stability of CTGs, however, the mechanical strength significantly decreases owing to the increasing open porosity and the decreasing content of hydration products. Based on the compressive strength and volume contents of cement in CTGs, the cost and embodied CO2 analyses indicate that the use of BFA in CTGs brings significant economic and environmental benefits.